2020
DOI: 10.1177/1129729820938202
|View full text |Cite
|
Sign up to set email alerts
|

Simulation training to improve aseptic non-touch technique and success during intravenous cannulation—effect on hospital-acquired blood stream infection and knowledge retention after 6 months: The snowball effect theory

Abstract: Background: Intravenous cannulation is a common procedure and a valuable skill in the neonatal intensive care unit. Standardized procedure and personnel training are needed in the unit to prevent hospital-acquired blood stream infections. Hence, we evaluated the effect of training using a low-fidelity simulation on the improvement of the aseptic non-touch technique during intravenous cannulation and knowledge retention after 6 months. Methods: The study was conducted in a tertiary care neonatal unit from June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…However, aseptic technique was incorporated into simulation‐based training and required to be demonstrated before the beginning of live‐case training. Simulation‐based training in aseptic technique for PIVC insertion has been previously demonstrated to improve technique and knowledge retention 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, aseptic technique was incorporated into simulation‐based training and required to be demonstrated before the beginning of live‐case training. Simulation‐based training in aseptic technique for PIVC insertion has been previously demonstrated to improve technique and knowledge retention 33 …”
Section: Discussionmentioning
confidence: 99%
“…Simulation-based training in aseptic technique for PIVC insertion has been previously demonstrated to improve technique and knowledge retention. 33 Supervisors and JMOs were contained within the same hospital, and results may not be generalisable to environments where both parties are not collocated. Also uncertain is the most beneficial timeframe to provide feedback to newly trained staff.…”
Section: Limitations and Generalisabilitymentioning
confidence: 99%
“…Several studies have demonstrated the effectiveness of checklists for preventing VAP and CRB (Hernández‐Aceituno et al., 2020; Kellie et al., 2014; Li et al., 2018; Radhakrishnan et al., 2021; Wichmann et al., 2018), and some have even found a decrease in infection rates after implementing simulation‐based training (Balachander et al., 2021; Barsuk et al., 2015; Behzadi et al., 2019; Gerolemou et al., 2014). To date, we have only found one questionnaire that assesses both knowledge and skills in preventing VAP (Jansson et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Team-based learning models using a simulated clinical environment have become part of the training of physicians and clinical staff. 7 8 Simulation provides a protected space for providers to test their individual knowledge and assess how well the team works in a replicated clinical scenario. It can help with the development and implementation of a crisis management plan where all team members effectively recognise their roles while managing rare clinical complications.…”
Section: Introductionmentioning
confidence: 99%